HOST NATIONS AT A CROSSROADS: UNPACKING THE SOCIO-POLITICAL DETERMINANTS OF HOST ATTITUDES TOWARD IMMIGRANTS AND REFUGEES - (:unkn) unknown (My University, 2024)
This dissertation investigates the complex interplay between several socio-political factors and native attitudes toward migrants by leveraging distinct survey experiments across three chapters. Particularly, it explores the roles of three novel mechanisms within the broader socio-political context that are often overlooked in the relevant literature: resentment, political threat perceptions, and social proximity. The results make significant contributions to the literature by providing new insights into these mechanisms. First, resentment, driven by perceived unfair resource distribution, amplifies natives' demands for refugee repatriation. Results also suggest that simply improving economic conditions or promoting contact may not be sufficient to change anti-migrant attitudes as resentment remains a strong driver of attitudes across different specifications. Second, natives not only harbor economic and cultural concerns but also political threat perceptions regarding migration. Thus, they prefer immigrants with shared party identities to come and live in their countries to tip the political balance in their favor. Finally, natives prefer living closer to politically like-minded immigrants, but they also think strategically about where these immigrants should settle. They overwhelmingly choose expected in-party members to go and live in politically volatile places to, once again, influence political outcomes. Overall, findings highlight how conventional determinants of attitude formation (i.e., economic, cultural) converge with socio-political factors, and accordingly influence native perceptions on migration.
Keywords: Attitudes; Balance of power; Immigration; Party ID; Refugee; Survey experiment